COMPETENCE-ORIENTED LEARNING AND THE ASSESSMENT OF EDUCATIONAL OUTCOMES - Yangiboyeva Oysora Qahramon qizi (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Competence-oriented learning focuses on the development of practical skills, applicable knowledge, and personal abilities that enable students to function effectively in real-life contexts. This approach ensures that educational outcomes are measurable, transparent, and relevant to societal and professional demands. The present article examines the fundamental principles of competence-based education and analyzes effective methods for assessing learning outcomes. Additionally, it highlights the advantages and challenges associated with the practical implementation of this educational approach.